Preparation method and application of foamy copper loaded noble metal catalyst

By using a method for preparing noble metal catalysts supported on copper foam, the problems of low selectivity and efficiency of existing electrocatalysts in the reduction of nitro compounds have been solved. This method enables the efficient and environmentally friendly reduction of chloronitrobenzene to chloroaniline, and is suitable for the selective reduction reaction of chloronitrobenzene by electrocatalysis.

CN119265602APending Publication Date: 2025-01-07CHONGQING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411526912.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing electrocatalysts suffer from low selectivity for target products and low Faraday efficiency in the reduction of nitro compounds, and traditional reduction methods pose safety hazards and generate a lot of waste.

Method used

A precious metal catalyst supported on copper foam was prepared by etching and immersion in a precious metal solution to increase the active sites and electrochemical active specific surface area. The catalyst was then used to electrocatalytically reduce chloronitrobenzene to chloroaniline using renewable energy.

Benefits of technology

It achieves highly selective and high Faradaic efficiency reduction of chloronitrobenzene, is safe and environmentally friendly, reduces waste emissions, and has good economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265602A_ABST
    Figure CN119265602A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a foamy copper supported noble metal catalyst, and belongs to the technical field of electro-catalysis. The foamy copper loaded noble metal catalyst is prepared by etching the foamy copper and soaking and reducing the foamy copper in the noble metal solution, the preparation process is simple, and the noble metal loading capacity is low. The prepared foamy copper loaded noble metal is used as an electrocatalyst for selective reduction reaction of chloronitrobenzene, dechlorination can be avoided, chloronitrobenzene is successfully reduced into chloronitrobenzene, and under the current density of 50mA. Cm <-2 >, the selectivity of the catalyst can reach 93% or above, the Faraday efficiency can reach 94% or above, the reactant conversion rate can reach 31% or above, and the selectivity of the catalyst can reach 93% or above, the Faraday efficiency can reach 94% or above. Good electro-catalysis application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a preparation method and application of a foam copper-loaded noble metal catalyst. Background Art

[0002] Chloroaniline (CANs) is an important class of chemical intermediates, which are widely used in the synthesis of medicines, pesticides, dyes, pigments, etc. CANs are mainly prepared by the reduction of chloronitrobenzene. Common reduction methods include: (1) iron powder reduction method, which is mature and simple to operate, but requires a large amount of iron powder, has low selectivity for the target product, and produces a large amount of wastewater and waste residue; (2) hydrazine hydrate reduction method, which has a high yield, but hydrazine hydrate is expensive and highly toxic; (3) alkali sulfide reduction method, which has an easy separation of the product and a short production cycle, but a low yield and produces a large amount of wastewater; (4) thermal catalytic hydrogenation reduction method, which has an easy separation of the product and the catalyst system, a recyclable catalyst, and low waste discharge, but is prone to dechlorination, and requires other process flows to obtain exogenous hydrogen, requires a high hydrogen pressure, and has safety issues; (5) electrocatalytic reduction method, which directly uses water as the hydrogen source and uses "green electricity" generated by renewable energy (such as solar energy, wind energy, etc.) as the power source. It is safe, environmentally friendly and has good economic benefits, and has received widespread attention in recent years.

[0003] The key to the electrocatalytic reduction method is to choose a suitable electrocatalyst. The catalysts for the electrocatalytic reduction of nitro compounds reported in the literature mainly include graphene-loaded Ag (Wenqian Li et al.ACS Applied Materials&Interfaces 2022, 14, 25478-25489), nitrogen-doped carbon-loaded Fe, Co and Cu (Nick Daems et al.Applied Catalysis B:Environmental 2018, 226: 509-522), and activated carbon-loaded Cu-based alloys (XiaSheng et al.ChemElectroChem 2014, 1, 1198-1210). These catalysts for the electrocatalytic reduction of nitro compounds have problems such as low selectivity of the target product and low Faraday efficiency. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a preparation method and application of a foam copper-supported noble metal catalyst, which has the characteristics of high conversion rate, high selectivity and high Faraday efficiency.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] Technical purpose 1: A method for preparing a foam copper-supported noble metal catalyst, comprising the following steps:

[0007] The copper foam is acid-washed, water-washed, alcohol-washed, and air-dried to obtain CF;

[0008] Etching the CF to obtain an eCF;

[0009] The eCF is immersed in a noble metal solution to react, thereby obtaining a foam copper-supported noble metal catalyst.

[0010] Further, the acid used in the pickling process is dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid; and / or;

[0011] The alcohol used in the alcohol washing process is methanol, ethanol, n-propanol or isopropanol.

[0012] Furthermore, the etchant used in the etching process is dilute nitric acid, FeCl3 solution or Fe(NO3)3 solution; the concentration of the etchant is 0.1-2 mol·L -1 ; The etching time is 0.5-10h.

[0013] Furthermore, the noble metal solution is a palladium dichloride solution, a chloroplatinic acid solution, a chloroauric acid solution, a ruthenium trichloride solution, a rhodium trichloride solution or a silver nitrate solution.

[0014] Furthermore, the immersion time is 2 hours; the mass ratio of the eCF to the noble metal in the noble metal solution is 1000:(1-3).

[0015] Technical purpose 2: A copper foam loaded precious metal catalyst prepared by the above preparation method, wherein the loading amount of the precious metal on the copper foam is 0.05-1wt%.

[0016] Technical purpose three: An application of the foam copper loaded precious metal catalyst in the electrocatalytic selective reduction of chloronitrobenzene to chloroaniline.

[0017] Furthermore, the electrocatalytic reaction is carried out in an electrolytic cell, the foam copper loaded with precious metal catalyst is used as the working electrode, the platinum mesh is used as the counter electrode, the saturated calomel electrode is used as the reference electrode, and the electrolytic solution is used as the concentration of 0.2 mol·L -1 of sodium perchlorate ethanol aqueous solution, separated by Nafion 117 proton exchange membrane.

[0018] Furthermore, during the electrocatalytic reaction, the concentration of chloronitrobenzene is 0.5-30 mg·mL -1 .

[0019] Furthermore, the chloronitrobenzene is any one of p-chloronitrobenzene, o-chloronitrobenzene, m-chloronitrobenzene, 2,5-dichloronitrobenzene, 3,4-dichloronitrobenzene, 3-chloro-4-fluoronitrobenzene and 2,4,5-trichloronitrobenzene.

[0020] Compared with the prior art, the present invention has the following advantages and technical effects:

[0021] (1) The present invention prepares a foam copper-loaded precious metal catalyst by etching the foam copper and immersing and reducing the foam copper in a precious metal solution. The preparation process is simple and the precious metal loading is low.

[0022] (2) The present invention uses the prepared copper foam loaded with precious metal as an electrocatalyst for the selective reduction reaction of chloronitrobenzene, which can avoid dechlorination and efficiently reduce chloronitrobenzene to chloroaniline at 50 mA cm -2 Under the current density, the selectivity of the catalyst can reach more than 93%, the Faraday efficiency is more than 94%, and the reactant conversion rate is more than 31%, which has good prospects for electrocatalytic application. This is because etching the copper foam and loading the precious metals, which produces more active sites, increases the electrochemical active specific surface area, reduces the charge transfer resistance, and modulates the adsorption of chloronitrobenzene on the catalyst, so that it can effectively use electrolysis to produce hydrogen source H* to generate highly selective chloroaniline.

[0023] (3) The present invention directly uses water as a hydrogen source and "green electricity" generated by renewable energy (such as solar energy, wind energy, etc.) as a power source to electrochemically reduce chloronitrobenzene to prepare chloroaniline, which is safe, environmentally friendly and sustainable. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0025] Figure 1 X-ray powder diffraction spectra of CF, eCF, and Ag / eCF catalysts prepared in Example 1, Example 3, and Example 6;

[0026] Figure 2 Electron scanning micrographs of CF, eCF, Ag / eCF prepared in Example 1, Example 3 and Example 6, and element distribution diagram of Ag / eCF; a is an electron scanning micrograph of CF, b is an electron scanning micrograph of eCF, c and d are electron scanning micrographs of Ag / eCF, e is an elemental mixed distribution diagram of Cu and Ag, f is an elemental distribution diagram of Cu, and g is an elemental distribution diagram of Ag;

[0027] Figure 3CV curves and C of CF (a), eCF (b), and Ag / eCF catalyst (c) prepared in Example 1, Example 3, and Example 6 at different scan rates dl The value (d) is obtained from the current density and the scan rate. DETAILED DESCRIPTION

[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0033] A method for preparing a foam copper-supported noble metal catalyst comprises the following steps:

[0034] (1) washing the copper foam with acid, water, and alcohol, and drying it to obtain CF;

[0035] (2) etching the CF to obtain an eCF;

[0036] (3) The eCF is immersed in a noble metal solution for reduction to obtain a foam copper-supported noble metal catalyst.

[0037] In step (1) of the following preferred embodiment of the present invention, the acid used in the pickling process is dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid. The purpose of pickling is to remove the metal oxide layer on the surface of the foam copper without damaging the foam copper matrix. Therefore, the present invention uses dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid with lower concentration for pickling to achieve the purpose; as an example, dilute hydrochloric acid is used for pickling in the following embodiments.

[0038] The purpose of alcohol washing is to remove oily substances on the surface of the copper foam. In the embodiment of the present invention, the alcohol used in the alcohol washing process includes but is not limited to methanol, ethanol, n-propanol or isopropanol; as an example, anhydrous ethanol is used to wash the copper foam in the following embodiments.

[0039] In step (2) of the following preferred embodiment of the present invention, the etchant used in the etching process is dilute nitric acid, FeCl3 solution or Fe(NO3)3 solution. The purpose of etching is to roughen the surface of the copper foam, generate more active sites, increase the electrochemical active specific surface area, and reduce the charge transfer resistance. In the following embodiment, FeCl3 solution is used as an example. The concentration of the etchant is 0.1-2 mol·L -1 The preferred concentration is 0.5 mol·L -1 ; The etching time is 0.5-10h, preferably 2h.

[0040] In the following preferred embodiment step (3) of the present invention, the noble metal solution is a palladium dichloride solution, a chloroplatinic acid solution, a chloroauric acid solution, a ruthenium trichloride solution, a rhodium trichloride solution or a silver nitrate solution, preferably a silver nitrate solution. The soaking time is 2 hours; the mass ratio of the eCF to the noble metal in the noble metal solution is 1000:(1-3), preferably 1000:2.

[0041] The foam copper-supported noble metal catalyst is prepared by the above-mentioned preparation method, and the loading amount of the noble metal on the foam copper is 0.05-1wt%, preferably 0.2%.

[0042] The application of the foam copper supported noble metal catalyst in the electrocatalytic selective reduction of chloronitrobenzene to chloroaniline. The chloronitrobenzene is any one of p-chloronitrobenzene, o-chloronitrobenzene, m-chloronitrobenzene, 2,5-dichloronitrobenzene, 3,4-dichloronitrobenzene, 3-chloro-4-fluoronitrobenzene and 2,4,5-trichloronitrobenzene. The following embodiments of the present invention use p-chloronitrobenzene.

[0043] The electrocatalytic reaction is carried out in an H-type electrolytic cell, with a copper foam loaded with a noble metal catalyst as a working electrode, a platinum mesh as a counter electrode, a saturated calomel electrode as a reference electrode, and an electrolytic solution of 0.2 mol·L -1 Sodium perchlorate ethanol aqueous solution (volume ratio of ethanol to water 5:1), separated by Nafion 117 proton exchange membrane. During the electrocatalytic reaction, the concentration of chloronitrobenzene is 0.5-30 mg·mL -1 In some preferred embodiments, the concentration of chloronitrobenzene is 1-20 mg·mL -1 In a more preferred embodiment, the concentration of chloronitrobenzene is 2 mg mL -1 . The current density is 30-70mA·cm -2 , preferably 50 mA·cm -2 .

[0044] The raw materials used in the present invention are all purchased from the market.

[0045] The technical solution of the present invention is further illustrated by the following embodiments.

[0046] Example 1

[0047] A method for preparing CF comprises the following steps:

[0048] The cut copper foam (10×15×1 mm) was cleaned with 3 mol / L hydrochloric acid, deionized water, and anhydrous ethanol for 10 min each by ultrasonic cleaning, and then dried to obtain CF.

[0049] Example 2

[0050] A method for preparing eCF comprises the following steps:

[0051] (1) Take the cut copper foam (10×15×1 mm) and use 3 mol / L hydrochloric acid, deionized water, and anhydrous ethanol to ultrasonically clean for 10 min each, and dry it to obtain CF;

[0052] (2) The obtained CF was immersed in 20 mL, 0.3 mol / L FeCl3 solution for 2 h for etching, rinsed with deionized water, and dried at 60°C for 2 h to obtain eCF.

[0053] Example 3

[0054] Same as Example 2, except that the concentration of the FeCl3 solution in step (2) is 0.5 mol / L.

[0055] Example 4

[0056] Same as Example 2, except that the concentration of the FeCl3 solution in step (2) is 0.7 mol / L.

[0057] Example 5

[0058] A method for preparing a foam copper-supported noble metal catalyst comprises the following steps:

[0059] (1) Take the cut copper foam (10×15×1 mm) and use 3 mol / L hydrochloric acid, deionized water, and anhydrous ethanol to ultrasonically clean for 10 min each, and dry it to obtain CF;

[0060] (2) The obtained CF was immersed in 20 mL, 0.5 mol / L FeCl3 solution for 2 h for etching, rinsed with deionized water, and dried at 60 °C for 2 h to obtain eCF;

[0061] (3) eCF was added into a silver nitrate solution in a mass ratio of eCF to Ag element of 1000:1 and immersed for 2 h, then rinsed with deionized water and dried at 60° C. for 2 h to obtain Ag / eCF, i.e., foam copper loaded with precious metal catalyst.

[0062] Example 6

[0063] The same as Example 5, except that the mass ratio of eCF to Ag in step (3) is 1000:2. The specific technical scheme is as follows:

[0064] A method for preparing a foam copper-supported noble metal catalyst comprises the following steps:

[0065] (1) Take the cut copper foam (10×15×1 mm) and use 3 mol / L hydrochloric acid, deionized water, and anhydrous ethanol to ultrasonically clean for 10 min each, and dry it to obtain CF;

[0066] (2) The obtained CF was immersed in 20 mL, 0.5 mol / L FeCl3 solution for 2 h for etching, rinsed with deionized water, and dried at 60 °C for 2 h to obtain eCF;

[0067] (3) eCF was added into a silver nitrate solution in a mass ratio of eCF to Ag of 1000:2 and immersed for 2 h, then rinsed with deionized water and dried at 60° C. for 2 h to obtain Ag / eCF, i.e., foam copper loaded with precious metal catalyst.

[0068] Example 7

[0069] The same as Example 5, except that the mass ratio of eCF to Ag in step (3) is 1000:3. The specific technical scheme is as follows:

[0070] A method for preparing a foam copper-supported noble metal catalyst comprises the following steps:

[0071] (1) Take the cut copper foam (10×15×1 mm) and use 3 mol / L hydrochloric acid, deionized water, and anhydrous ethanol to ultrasonically clean for 10 min each, and dry it to obtain CF;

[0072] (2) The obtained CF was immersed in 20 mL, 0.5 mol / L FeCl3 solution for 2 h for etching, rinsed with deionized water, and dried at 60 °C for 2 h to obtain eCF;

[0073] (3) eCF was added into a silver nitrate solution in a mass ratio of eCF to Ag of 1000:3 and immersed for 2 h, rinsed with deionized water, and dried at 60° C. for 2 h to obtain Ag / eCF, i.e., foam copper loaded with precious metal catalyst.

[0074] Example 8

[0075] Same as Example 6, except that in step (2), the etchant is replaced by Fe(NO3)3 solution in equal volume and concentration.

[0076] Example 9

[0077] The same as Example 6, except that in step (3), silver nitrate is replaced by palladium dichloride solution, that is, the mass ratio of eCF to palladium is 1000:2.

[0078] Example 10

[0079] The same as Example 6, the only difference is that in step (3), silver nitrate is replaced by ruthenium trichloride solution, that is, the mass ratio of eCF to ruthenium is 1000:2.

[0080] Embodiment 11

[0081] The same as Example 6, except that in step (3), silver nitrate is replaced by rhodium trichloride solution, that is, the mass ratio of eCF to rhodium is 1000:2.

[0082] Application Example 1

[0083] The electrocatalytic reaction was carried out in an H-type electrolytic cell, with the catalyst prepared in Example 1-11 as the working electrode, the platinum mesh as the counter electrode, the saturated calomel electrode as the reference electrode, and the electrolytic solution as 0.2 mol·L -1 Sodium perchlorate ethanol aqueous solution (volume ratio of ethanol to water 5:1), separated by Nafion 117 proton exchange membrane, 2 mg mL -1 p-Chloronitrobenzene, 50mA·cm -2 The reaction was carried out for 4 h at the current density. The results are shown in Table 1.

[0084] Table 1 Electrocatalytic reduction of p-chloronitrobenzene to prepare p-chloroaniline reaction results

[0085]

[0086] Note: p-CNB is p-chloronitrobenzene, p-CAN is p-chloroaniline, AN is aniline (the same below).

[0087] As can be seen from Table 1, by comparing Examples 2-4, it is found that the concentration of the etchant will affect the catalytic performance of the catalyst to p-chloronitrobenzene, and the catalytic performance is optimal when the concentration of the etchant is 0.5 mol / L; by comparing Examples 5-7, it is found that the amount of precious metal added will affect the catalytic performance of p-chloronitrobenzene, and the catalytic performance is optimal when the mass ratio of eCF to precious metal Ag is 1000:2.

[0088] Application Example 2

[0089] The effect of current density on the reaction performance of 0.2% Ag / eCF catalyst in Example 6 for electrocatalytic hydrogenation of p-chloronitrobenzene to p-chloroaniline was investigated. This application example is the same as application example 1, except that the current densities are 30, 50 and 70 mA·cm -2 , the results are shown in Table 2.

[0090] Table 2 Results of electrocatalytic reduction of p-chloronitrobenzene to p-chloroaniline over 0.2% Ag / eCF at different current densities

[0091]

[0092] It can be seen from Table 2 that current density is one of the factors affecting the electrocatalytic performance. With the increase of current density, the electrocatalytic performance first increases and then decreases. It is found that when the current density is 50 mA cm -2 The electrocatalytic performance is optimal.

[0093] Application Example 3

[0094] The effect of the 0.2% Ag / eCF catalyst in Example 6 on the reaction performance of p-chloronitrobenzene electrocatalytic hydrogenation to p-chloroaniline was investigated. This application example is the same as application example 1, except that the p-chloronitrobenzene concentrations are 1, 2, 4, 8, and 20 mg·mL -1 , the results are shown in Table 3.

[0095] Table 3 Results of electrocatalytic reduction of p-chloronitrobenzene to prepare p-chloroaniline using 0.2% Ag / eCF catalyst at different p-chloronitrobenzene concentrations

[0096]

[0097]

[0098] It can be seen from Table 3 that the concentration of p-chloroaniline is one of the factors affecting the electrocatalytic performance. With the increase of p-chloroaniline concentration, the electrocatalytic performance first increases and then decreases. It is found that when the concentration of p-chloroaniline is 2 mg mL -1 The electrocatalytic performance is optimal.

[0099] Figure 1 The X-ray powder diffraction spectra of the catalysts prepared in Example 1, Example 3 and Example 6 show that CuCl is generated on the surface of the copper mesh after etching with a ferric chloride solution, and CuO is generated after loading Ag.

[0100] Figure 2 The electron scanning microscope images of the catalysts prepared in Example 1, Example 3 and Example 6 and the element distribution diagram of Ag / eCF show that the surface roughness of the copper foam increases after etching, and after the step of impregnating Ag, the Ag element is evenly distributed on the copper foam matrix, indicating that the metal element Ag is successfully loaded.

[0101] Figure 3 CV curves and C of the catalysts prepared in Example 1, Example 3 and Example 6 at different scanning rates dl As can be seen from the figure, the C dl Value (5.22mF·cm -2 ) is significantly greater than CF (0.79 mF·cm -2 ) and eCF (1.44mF·cm -2 ), indicating that 0.2%Ag / eCF has a larger electrochemically active specific surface area.

[0102] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a foam copper-supported noble metal catalyst, characterized in that: The following steps are involved: The copper foam is acid-washed, water-washed, alcohol-washed, and air-dried to obtain CF; Etching the CF to obtain an eCF; The eCF is immersed in a noble metal solution to react, thereby obtaining a foam copper-supported noble metal catalyst.

2. The method for preparing a foam copper-supported noble metal catalyst according to claim 1, characterized in that: The acid used in the pickling process is dilute hydrochloric acid, dilute sulfuric acid or dilute nitric acid; and / or; The alcohol used in the alcohol washing process is methanol, ethanol, n-propanol or isopropanol.

3. The method for preparing a foam copper-supported noble metal catalyst according to claim 1, characterized in that: The etchant used in the etching process is dilute nitric acid, FeCl3 solution or Fe(NO3)3 solution; the concentration of the etchant is 0.1-2 mol·L -1 ; The etching time is 0.5-10h.

4. The method for preparing a foam copper-supported noble metal catalyst according to claim 1, characterized in that: The noble metal solution is a palladium dichloride solution, a chloroplatinic acid solution, a chloroauric acid solution, a ruthenium trichloride solution, a rhodium trichloride solution or a silver nitrate solution.

5. The method for preparing a foam copper-supported noble metal catalyst according to claim 1, characterized in that: The immersion time is 2 hours; the mass ratio of the eCF to the noble metal in the noble metal solution is 1000:(1-3).

6. A foam copper-supported noble metal catalyst prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The loading amount of the noble metal on the copper foam is 0.05-1 wt %.

7. Use of the foam copper supported noble metal catalyst as claimed in claim 6 in the electrocatalytic selective reduction of chloronitrobenzene to chloroaniline.

8. The use according to claim 7, characterized in that: The electrocatalytic reaction is carried out in an electrolytic cell, wherein the foam copper loaded with precious metal catalyst is used as the working electrode, the platinum mesh is used as the counter electrode, the saturated calomel electrode is used as the reference electrode, and the electrolytic solution has a concentration of 0.2 mol·L -1 Sodium perchlorate ethanol aqueous solution is separated by Nafion117 proton exchange membrane.

9. The use according to claim 7, characterized in that: During the electrocatalytic reaction, the concentration of chloronitrobenzene is 0.5-30 mg·mL -1 .

10. The use according to claim 7, characterized in that: The chloronitrobenzene is any one of p-chloronitrobenzene, o-chloronitrobenzene, m-chloronitrobenzene, 2,5-dichloronitrobenzene, 3,4-dichloronitrobenzene, 3-chloro-4-fluoronitrobenzene and 2,4,5-trichloronitrobenzene.